Dynamic Stability Behaviour of Lattice Domes with Substructures. Issue 1 (March 2014) - Sun, Jianheng; Li, Hongmei; Nooshin, Hoshyar; Parke, Gerard A.R.
Dynamic behaviour is one of the main controlling factors for the design of large single-layer lattice dome structures. Considering a single-layer lattice dome and its supporting frame as an integral whole, this paper investigates the dynamic stability behaviour of the dome under seismic loads. In the analysis, the initial geometric imperfections, together with geometric and material nonlinearities, are considered. A factor expressing the degree of stiffness of the supporting frame is also used in the analysis. The effects of supporting frames of different stiffness and different rise to span ratios of the domes are also investigated. The results of the investigation show that the stiffness of the substructure can play a very important role in the dynamic stability behaviour of the dome.